Low-Temperature Atomic Layer Deposition of High-k SbOx for Thin Film Transistors - Yang, Jun; Bahrami, Amin; Ding, Xingwei; Zhao, Panpan; He, Shiyang; Lehmann, Sebastian; Laitinen, Mikko; Julin, Jaakko; Kivekas, Mikko; Sajavaara, Timo; Nielsch, Kornelius (Advanced Electronic Materials, 2022)
SbOx thin films are deposited by atomic layer deposition (ALD) using SbCl5 and Sb(NMe2)3 as antimony reactants and H2O and H2O2 as oxidizers at low temperatures. SbCl5 can react with both oxidizers, while no deposition is found to occur using Sb(NMe2)3 and H2O. For the first time, the reaction mechanism and dielectric properties of ALD-SbOx thin films are systematically studied, which exhibit a high breakdown field of ≈4 MV cm−1 and high areal capacitance ranging from 150 to 200 nF cm−2, corresponding to a dielectric constant ranging from 10 to 13. The ZnO semiconductor layer is integrated into a SbOx dielectric layer, and thin film transistors (TFTs) are successfully fabricated. A TFT with a SbOx dielectric layer deposited at 200 °C from Sb(NMe2)3 and H2O2 presents excellent performance, such as a field effect mobility (µ) of 12.4 cm2 V−1 s−1, Ion/Ioff ratio of 4 × 108, subthreshold swing of 0.22 V dec−1, and a trapping state (Ntrap) of 1.1 × 1012 eV−1 cm−2. The amorphous structure and high areal capacitance of SbOx boosts the interface between the semiconductor and dielectric layer of TFT devices and provide a strong electric field for electrons to improve the device mobility.
CRIS-Team Scopus Importer:2022-04-14
Keywords: atomic layer deposition; high-k dielectric; low temperature; oxide semiconductor; ToF-ERDA